Tax revenue econometric estimation - Mačiulaitytė, Elena; Rudzkis, Rimantas (Lietuvos matematikos rinkinys, 2003)
National budget tax revenue in relation with economic changes in Lithuania in 1995–2002 is analyzed in this article. There is also analyzed value added tax (VAT) as it brings the biggest share of Lithuanian National budget and economic factors that influence VAT revenue. Time series models of relational indicators of tax revenue are presented in this paper. Results of statistic hypotheses presented here reflect a quality and tendency of collection of VAT and tax revenue as a whole in different periods of time considering the economic situation in the country.